Evaluation of therapy in traumatic elderly falls to return autonomy and functional status - Christopher W Foote, MD, MS; Cheryl Vanier, PhD; Chaoyang Chen, MD, PhD; Carlos H Palacio, MD, FACS (Surgery Open Science, 2022)
Background: Traumatic falls among the elderly (≥65 years old) are the leading cause of injury, morbidity and mortality are increasing with rising medical costs. Methods: This is a retrospective medical record review of elderly mechanical fall patients (288 patients) admitted to an American College of Surgeons level II trauma center from January 2016 to January 2021. Demographics and comorbidities were determined, and physical/occupational therapy used to predict subsequent fall readmissions. Results: Out of 288 patients, 243 received therapy with 45 readmissions for subsequent falls. Age (P = .016), body mass index (P = .035), previous falls (P = .003), walker/cane use (P = .039), and dementia (P = .038) were predictive of readmission. Therapy was shown to benefit patients, but deferred therapy sessions were shown to be associated with prolonged hospitalization. Conclusion: Directed therapy may improve functionality and return autonomy to elderly mechanical fall patients admitted to trauma services.